Recent Progress in Fluorescent Probes For Metal Ion Detection - Li, Luanjing; Wang, Jiahe; Xu, Shihan; Li, Chunxia; Dong, Biao (Frontiers in Chemistry, 2022)
All forms of life have absolute request for metal elements, because metal elements are instrumental in various fundamental processes. Fluorescent probes have been widely used due to their ease of operation, good selectivity, high spatial and temporal resolution, and high sensitivity. In this paper, the research progress of various metal ion（Fe3+、Fe2+、Cu2+、Zn2+、Hg2+、Pb2+、Cd2+） fluorescent probes in recent years has been reviewed, and the fluorescence probes prepared with different structures and materials in different environments are introduced. It is of great significance to improve the sensing performance on metal ions. This research has a wide prospect in the application fields of fluorescence sensing, quantitative analysis, biomedicine and so on. This paper discusses about the development and applications of metal fluorescent probes in future.